Hubungan Perilaku Orang Tua dengan Early Childhood Caries Pada Anak Usia 2-3 Tahun di Kota Padang - Mutiara Hapka; Susi Susi; Aria Fransiska (Faculty of Dentistry Universitas Andalas, 2021)
Caries is a public health problem in the world. According to WHO, an estimated 60-90% of children experience caries. Caries in primary teeth is known as Early Childhood Caries (ECC). The prevalence of ECC in Bukittinggi in 2018 reached 69.2%. ECC often occurs, but less attention from parents, even though parents play an important role in forming behaviors that support or not oral health on children.The purpose of this study is to determine the relationship between parental behavior and Early Childhood Caries on children aged 2-3 years in Padang.The methods of this study used the cross sectional design, with the total sampel were 107 children aged 2-3 years in Padang. The location was selected through Multistage Random Sampling Method and samples was selected through Consecutive Sampling Method. Collecting data is using by questionares and intra-oral examination that were analyzed by Chi-Square test. The results of this study was prevalece of ECC in children aged 2 to 3 years in Padang is 72.9% and def-t index is 3.76. Parents who have a high level of knowledge about 59,8%, 84,1% have a good attitude, and about 63,6% have good practice toward health behavior. The result of analysis showed that p value between parental knowledge and ECC was 0.339, p value between parental attitude and ECC was 0.005 and p value between parental practice and ECC was 1.000. The conclusions of this study is there was no relation between parental knowledge and practice with ECC. There was a significant relation between parental attitude and EEC in children aged 2 to 3 years in Padang.